Natural fiber-reinforced polylactic acid, polylactic acid blends and their composites for advanced applications - Ilyas, R. A.; M. Y., M. Zuhri; A., Aisyah H.; M. R., M. Asyraf; A. Hassan, S.; Zainudin, E. S.; Salit, Mohd Sapuan; Sharma, S.; Bangar, S. P.; R., Jumaidin; Nawab, Y.; M. Faudzi, A. A.; et al. (Multidisciplinary Digital Publishing Institute, 2022)
Polylactic acid (PLA) is a thermoplastic polymer produced from lactic acid that has been chiefly utilized in biodegradable material and as a composite matrix material. PLA is a prominent biomaterial that is widely used to replace traditional petrochemical-based polymers in various applications owing environmental concerns. Green composites have gained greater attention as ecological consciousness has grown since they have the potential to be more appealing than conventional petroleum-based composites, which are toxic and nonbiodegradable. PLA-based composites with natural fiber have been extensively utilized in a variety of applications, from packaging to medicine, due to their biodegradable, recyclable, high mechanical strength, low toxicity, good barrier properties, friendly processing, and excellent characteristics. A summary of natural fibers, green composites, and PLA, along with their respective properties, classification, functionality, and different processing methods, are discussed to discover the natural fiber-reinforced PLA composite material development for a wide range of applications. This work also emphasizes the research and properties of PLA-based green composites, PLA blend composites, and PLA hybrid composites over the past few years. PLA’s potential as a strong material in engineering applications areas is addressed. This review also covers issues, challenges, opportunities, and perspectives in developing and characterizing PLA-based green composites.